DUKUNGAN SOSIAL DENGAN PROKRASTINASI AKADEMIK PADA SISWA SMA CENDEKIA - Nibras Ali Gunanjar; Dwi Nastiti (Jurnal Psikologi Poseidon, 2019)
This study aims to define whether there is a relationship between social support and academic procrastination in completing tasks for SMA 'Cendekia' Sidoarjo students. This research uses correlation quantitative conducted in SMA Cendekia with a total sample of 113 students, taken by saturated sampling. Data collection techniques in this study used two psychology scales models of Likert, namely the social support scale and the academic procrastination scale. These results write down that there is a negative relationship between social support and academic procrastination in completing tasks for SMA Cendekia Sidoarjo.